IDENTIFIKASI TELUR CACING ASCARIS LUMBRICOIDES PADA KEMANGI (OCIMUM BASILICUM L) YANG DIJUAL DI PASAR - Muslimin, Muslimin; Indriyani, Yeni; Sigalingging, Jamisten; Antara, Nyoman Yudi; Sitindaon, Rina SE (JURNAL KESEHATAN TERAPAN, 2021)
Ascaris lumbricoides is a roundworm which is a class of intestinal nematodes that are commonly found in tropical and subtropical areas where the condition of the area shows a low level of environmental hygiene. The prevalence of worm egg infection is generally transmitted through food, drinks and vegetables such as basil which is consumed raw as vegetables that are not clean in washing. This study aims to identify the eggs of Ascaris Lumbricoides worm in basil vegetables with samples obtained from the market. Experimental research method with qualitative laboratory examination with Flotation method to identify worm eggs. The population of all Basil vegetables are sold from vegetable traders in the market. Sampling is all basil vegetables from the market. Primary data generated from basil samples were observed. From the results of research conducted on basil vegetables showed negative results containing worm eggs, so basil is safe for consumption. Keywords: Ascaris lumbricoides, Basil, Worm eggs